Assessment of availability of trace elements in turf soil after biosolids application. (29th August 2022) - Johnston, Theresa; Tian, Guanglong; Voigt, Thomas; Lindo, Pauline; Cox, Albert; Granato, Thomas; Zhang, Heng; Podczerwinski, Ed
Abstract: Soil amendments rich in organic matter and micronutrients can benefit plants by increasing the availability of micronutrients. To evaluate changes in the availability of trace elements in biosolids‐amended soil, soil and plant samples were collected from six managed turfgrass locations across the Chicago metropolitan area that received air‐dried biosolids topdressing at two rates: 2.2 Mg ha –1 per application (low biosolids rate), 11 Mg ha –1 per application (high biosolids rate), and urea 48.8 kg ha –1 total N per application (control). The low and high rates refer to biosolids total N and plant‐available N, respectively, considered for meeting the turfgrass N recommendation. Biosolids and urea application was conducted for each year of 2006–2008 with multiple applications per year. For micronutrients tested, biosolids application increased concentrations of soil‐available (Mehlich‐3 extraction) Zn (29.5 ± 2.9 mg kg –1, mean ± SE) and Cu (9.0 ± 0.6 mg kg –1 ) for the high rate vs. the control (10.4 ± 2.9 mg kg –1 for Zn and 6.1 ± 0.7 mg kg –1 for Cu). Soil‐available Mn, Fe, and Mo in the biosolids treatments did not differ from the control. Application of biosolids increased turf plant Cu, Zn, Mn, and Mo concentrations for both 2007 and 2008 and Fe for 2007 vs. the control with statistical significance at the high rate of biosolids. Topdressing with a plant‐available N‐based application rate for biosolids increased turfgrass nutrition of micronutrients without a concern of heavy metals. Core Ideas: Biosolids topdressing improved Cu and Zn soil availability and turf plant concentrations of Cu, Zn, Mn, and Mo. N‐based biosolids application rate provides sufficient plant available micronutrients for turfgrass. Biosolids application did not lead to a concern of heavy metals in turf soil.